Effect of melatonin supplementation on the gingival health and lipid profiles in obese periodontitis patients - Ismail, Hussam Sami; Mahmood , Maha Sh. (Journal of Baghdad College of Dentistry, 2022)
Background: Obesity increases the host’s susceptibility by modulating the immune and inflammatory systems in a manner that predisposes to inflammatory tissue destruction and leaves an individual at greater risk of periodontitis. Melatonin is a pineal secretory product involved in numerous actions, such as regulation of internal biological clocks and energy metabolism, and it functions as an antioxidant and anti-inflammatory agent. There exists a substantial amount of evidence supporting the beneficial effect of melatonin supplementation on obesity and its complications. Aim of the study: To investigate the effects of systemic melatonin intake on periodontal health status and lipid profiles in obese periodontitis patients. Subjects and methods: Subjects included in the study were distributed into the following groups: Group I, 20 subjects with normal weight and healthy periodontium (controls) not subjected to any treatment. Group II: 30 obese periodontitis patients subjected to scaling and root planing (SRP) only. Group III: 30 obese periodontitis patients subjected to SRP and supplemented with 5mg melatonin tablets for 1 month. Study groups subjected to estimation of plaque index (PLI), bleeding on probing (BOP), cholesterol (chol), triglycerides (TG), high-density lipoprotein (HDL) and low-density lipoprotein (LDL) at baseline and after 4 weeks recall visit. Results: Regarding the clinical parameters, the second visit exhibited decreasing in all parameters in both study groups except BOP score 0 were it increased significantly. Regarding lipid profiles, the second visit showed decreasing in all profiles except HDL where it increased in both study groups with a significant difference. All correlations between lipid profiles in recall visit in both study groups exhibited a positive significant correlation between chol and TG, chol and LDL, LDL and TG in group III. In group II all results exhibited a positive significant correlation, whereas the only strong negative correlation was found between chol and HDL, HDL and LDL. Conclusion: Daily supplementation with 5mg melatonin tab significantly improved periodontal health and reduced chol, TG, LDL with increasing HDL.